Adventures in coding - Holland, Eva; Minnick, Chris (John Wiley & Sons, Inc, 2016)
Learn to code the fun way with nine real projects for true beginners Adventures in Coding is written specifically for young people who want to learn how to code, but don't know where to begin. No experience? No problem! This book starts from the very beginning to take you from newbie to app-builder in no time